2008
DOI: 10.1253/circj.cj-08-0393
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Prediction of Angiographic Spasm Provocation Using Trans-Thoracic Doppler Echocardiography in Patients With Coronary Spastic Angina

Abstract: oronary spastic angina (CSA) causes myocardial ischemia at rest by abnormal contraction of epicardial coronary arteries without organic stenosis, which often occurs between midnight and early in the morning. 1 The diagnostic accuracy of noninvasive modalities for CSA, such as the cold pressor test or hyperventilation test, has been low, 2 so angiographic assessment in conjunction with spasm-provocation by intracoronary injection of acetylcholine has been the most standard, albeit an invasive, method of diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Interestingly, however, TFC values were unchanged in the positive ACh group when intra-coronary ISDN was administrated in the present study. We previously reported that the patients with a positive result of the ACh provocation test had significantly higher resting Tmn values compared with those without (1.18 ± 0.51 vs. 0.75 ± 0.31 s, p < 0.001) [10], as well as other previous studies [9,32,33]. In addition, a recent European multi-center study evaluating the diagnostic ability of the "ACh rechallenge" to detect coexisting microvascular spasm among patients with epicardial spasm showed that micro-vascular spasm remained after intracoronary administration of ISDN during ACh provocation test in approximately 70% of study patients [34].…”
Section: Discussionsupporting
confidence: 69%
“…Interestingly, however, TFC values were unchanged in the positive ACh group when intra-coronary ISDN was administrated in the present study. We previously reported that the patients with a positive result of the ACh provocation test had significantly higher resting Tmn values compared with those without (1.18 ± 0.51 vs. 0.75 ± 0.31 s, p < 0.001) [10], as well as other previous studies [9,32,33]. In addition, a recent European multi-center study evaluating the diagnostic ability of the "ACh rechallenge" to detect coexisting microvascular spasm among patients with epicardial spasm showed that micro-vascular spasm remained after intracoronary administration of ISDN during ACh provocation test in approximately 70% of study patients [34].…”
Section: Discussionsupporting
confidence: 69%
“…3 Thus, he proposed "an increased tonus" at the site of a subcritical stenosis as the likely cause of the syndrome. 7 Subsequently, variant angina was described by Cheng et al also in patients with angiographically normal coronary arteries and defined "the variant of the variant", 8 thus falsifying the paradigm that a stenosis was required for the development of spasm. However, 15 years after the publication of the Prinzmetal report, there was a prevailing scepticism at the World Congress of Cardiology in Buenos Aires in 1974, after the presentation of the angiographic findings of 3 cases of occlusive spasm abolished by nitrates by Maseri's group: most of the audience believed that spasm was an artefact induced by the catheter!…”
Section: Variant Anginamentioning
confidence: 99%